2015
DOI: 10.1021/acs.jpcc.5b08713
|View full text |Cite
|
Sign up to set email alerts
|

Nanowetting of Graphene by Ionic Liquid Droplets

Abstract: The behavior of nanodroplets formed by amino acid based 1-ethyl-3-methylimidazolium glycine ionic liquid on graphene sheets was studied using classic molecular dynamics. Nanodroplets of different sizes were analyzed, and the contact angle was inferred. The ion–graphene interaction energy was calculated as a function of droplets size, together with the ions arrangement at the interface. Likewise, wetting of SiO2 and graphene supported on SiO2 by ionic liquid nanodroplets was also analyzed. Graphene wetting by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
48
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(55 citation statements)
references
References 52 publications
5
48
2
Order By: Relevance
“…The results here contrast with the ones obtained by Herrara et al 38 Firstly, in this work, no consistent drop size dependence on the contact angle was found. Most significantly however, is that the results here show wetting behavior that significantly deviates from a regular drop at a sheet interaction potential of 0.23 kJ mol -1 , whilst Herrara et al 38 reported contact angles of 48 and 80 degrees for drop sizes of 200 and 500 IL pairs respectively whilst using an even more strongly interacting sheet of ε = 0.2929 kJ mol -1 .…”
Section: Resultscontrasting
confidence: 99%
See 4 more Smart Citations
“…The results here contrast with the ones obtained by Herrara et al 38 Firstly, in this work, no consistent drop size dependence on the contact angle was found. Most significantly however, is that the results here show wetting behavior that significantly deviates from a regular drop at a sheet interaction potential of 0.23 kJ mol -1 , whilst Herrara et al 38 reported contact angles of 48 and 80 degrees for drop sizes of 200 and 500 IL pairs respectively whilst using an even more strongly interacting sheet of ε = 0.2929 kJ mol -1 .…”
Section: Resultscontrasting
confidence: 99%
“…The difference is seen between the energy values in Figure 3. For the interaction potential of 0.23 kJ mol -1 , simulation times in excess of 20 ns were required to reach equilibrium, this is a large increase over that reported by Herrara et al, 38 where less than 5 ns were required with a simulation temperature of 403 K. The differences in time required could possibly be partly explained by the temperature used in this work, 298 K, and it is also the differences in the liquid-liquid interactions between the two IL pairs used may also have played a role. pairs, which is expected due to its smaller size creating shorter diffusion paths for the ions.…”
Section: Resultsmentioning
confidence: 88%
See 3 more Smart Citations